Static Stress Analysis of Fork on Rubber Slab Lifting Aid using Finite Element Method - Khoirullah, Ananda Thomas; Sampurno, Rachmat Dwi; Sailon, Sailon; Ramadhoni, Tri Satya; Rizal, Syamsul; Yuliandi, Rizky Brillian (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The focus of this research is to simulate the static stress on the fork component of the tool to analyze the strength and feasibility of the design. The simulation used a method called Finite Element Method (FEA), which allows to find any problems before the prototype is made. The material used is ASTM A36 steel with a yield strength value of 250 MPa. The loading used is 300 kg with the direction of the force centered on the y-axis of the beam right in the middle of the object. With variable fork design dimensions that have been simplified in the form of 762x101.6x31.75 mm; 1219.2x127x44.45 mm; and 2133.6x152.4x50.8 mm, the distribution of analysis results consisting of maximum bending stress, moment, displacement, and factor of safety is obtained. The maximum bending stress values for designs A, B, and C in the simulation are 65.688 MPa; 42.891 MPa; and 47.897 MPa, respectively, with moment values of 1121.283 N.m; 1793.758 N.m; and 3139.592 N.m. Meanwhile, the displacement values in the simulation results for each design are 2.508 mm; 2.992 mm; and 8.948 mm, respectively, with factor of safety values of 3.8; 5.8; and 5.2. Static stress analysis on the fork design produces analytical calculation values and simulation calculations with small tolerances. Based on the results of these calculations, it is concluded that the most optimal fork design is design B because it has a lower value of maximum bending stress and displacement, and has a higher factor of safety value than other designs.